Analisis Tingkat Efisiensi Perbankan Dengan Pendekatan Non Parametrik Data Envelopment Analysis (DEA) (Studi Pada Bank Umum di Indonesia Tahun 2005-2011) - Wardana, Sandi Kusuma; hir, Djuma (Jurnal Ilmiah Mahasiswa FEB, 2013)
Financial institutions have an essential role in the developing countries’ economy. Banks as one of the financial institution are required to have a good performance, especially in competition environment between banks and one of important aspect in performance measurement is efficiency. The purpose of this study was to analyzes the efficiency performance of 13 Indonesian commercial banks listed in Indonesian Stock Exchange (IDX) with the research period of  2005 until 2011 and meet  the criteria established. Analysis of the data used are non-parametric methodology data envelopment analysis (DEA). According to results, the efficiency levels do not change very much between 2005 and 2011. The efficiency scores reached top level in 2011 for all banks. The results also show that there is no difference in efficiency between state owned and national private commercial banks in Indonesia. Keywords: banks efficiency, data envelopment analysis, Indonesian commercial banks.